A Study to Assess the Relationship between Sleep Quality and Quality of Life among IT Professionals at SRMIST, Kattankulathur, Kancheepuram District (International Journal of Nursing Education, 2019)
Aim: To assess and correlate the sleep quality and quality of life among IT Professionals. Method: The Research design adopted for the study was Non experimental descriptive–correlational Research design. Sample size for the study was 50.Non-probability convenient sampling technique was used to select the sample for the study. The tool consists of 3 sections Section A: Structured questionnaire was used to assess the demographic variables of IT Professionals. Section B: Pittsburgh Sleep Quality Index (PSQI) was used to assess the Sleep Quality Of IT Professionals. Section C: World Health Organization (WHO) Quality Of Life scale was used to assess the quality of life among Information Technology ( IT) Professionals. Result: The results revealed that out of 50 (14%) of IT Professionals had poor Quality of life, 20% of IT Professionals had Excellent Quality of life, 66% of IT Professionals had Good Quality of life. The result revealed that, The P-value of the Pearson’s correlation co-efficient is highly significant (since the P-value is lesser than 0.01) and there is significant positive relation (correlation) found between Sleep Quality and Quality of Life of IT Professionals. Conclusion: The study concludes that, out of 50 (70%) of IT Professionals had Good sleep quality, 30% of IT Professionals had poor sleep quality. It is clear that, if sleep quality is good for IT professionals then their Quality of life will be good.
Keywords: Assess, Sleep quality, Quality of life, IT Professionals